2015
DOI: 10.1039/c5tx00197h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mid-respiratory chain inhibition on mitochondrial function in vitro and in vivo

Abstract: Schematic showing the toxicological and adaptive effects of drug-induced respiratory chain inhibition in vivo; also highlighting unanticipated differences from observations made in vitro (in red).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…1A , see Methods). GSK932121A binds to the Qi site of CIII [ 23 ] and inhibits CIII catalytic activity in rodents [ 21 ] Prior work has demonstrated its toxic effects upon mitochondrial function in female Crl:CD(SD) rats when administered at a dose of 50 mg kg −1 i.p [ 21 ]. The dose used here is below that shown to invoke overt hepatotoxicity, with the aim being to exert mild CIII inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A , see Methods). GSK932121A binds to the Qi site of CIII [ 23 ] and inhibits CIII catalytic activity in rodents [ 21 ] Prior work has demonstrated its toxic effects upon mitochondrial function in female Crl:CD(SD) rats when administered at a dose of 50 mg kg −1 i.p [ 21 ]. The dose used here is below that shown to invoke overt hepatotoxicity, with the aim being to exert mild CIII inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Liver fibrosis associated with mitochondrial dysfunction has been shown to coincide with raised circulating lactate [ 27 29 ]; however, no rise in plasma lactate was observed here following hypoxic exposure or GSK932121A administration, either alone or in combination (Additional File 1 : Figure S1E). Administration of GSK932121A at 50 mg kg −1 has been associated with hepatic glycogen depletion [ 21 ], yet no change in hepatic glycogen storage was observed (Additional File 1 : Figure S1F). Together, this suggests that whilst 2 days of hypoxic exposure in combination with GSK932121A administration invoked hepatic stress, the dose used did not result in overt hepatotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs targeting the mitochondrial respiratory chain (MRC) are relatively well tolerated in normal tissues (Blecha et al 2017 ). Many in vitro studies may also be insensitive to mitochondrial toxicants as cells are kept in supra-physiological (e.g., 3–5 times higher than normal plasma levels) glucose concentrations (Blomme and Will 2016 ; Broom et al 2016 ; Perron et al 2013 ; Tilmant et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This in vivo effect was suggested to have resulted from the initial insult in combination with compensatory changes made by the tissue in order to maintain energy production. 35 Fan et al reported that a short-term incubation of mitochondria in vitro with the organic arsenical MOPIMP promoted the inhibition of respiratory chain complexes I, II, III and IV, and with damage to the respiration process. 19 The activity of complex IV, the terminal complex of the electron transport chain, was significantly destroyed even when treated with MOPIMP at a low concentration level.…”
mentioning
confidence: 99%